PP.27.14: EFFECT OF ALISKIREN ON VASCULAR REMODELING IN SMALL RETINAL CIRCULATION. (June 2015) - Ott, C.; Jumar, A.; Harazny, J.; Schmidt, S.; Schmieder, R.E.
Abstract : Objective: In hypertension changes in small arterial structure are characterized by an increased wall-to-lumen ratio (WLR). These adaptive processes are modulated by the renin angiotensin system (RAS). It is less clear whether direct renin inhibitors (DRIs) exert protective effects on small arteries in hypertensive patients. Design and method: In this double-blind, randomized, placebo-controlled study (www.clinicaltrials.gov: NCT01318395) 113 patients with primary hypertension were included. After 4 weeks of standardized open-label treatment with the angiotensin receptor blocker valsartan 320 mg (run-in phase), patients were randomized to additional therapy with either placebo or DRI aliskiren 300 mg for 8 weeks. Parameter of arteriolar remodeling was WLR of small retinal arterioles (80 – 140 μm) assessed non-invasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany). In addition, pulse wave analysis (SphygmoCor™, AtCor Medical, Australia) was performed and pulse pressure (PP) amplification determined (ratio of peripheral PP to central PP). Results: In the whole study population no clear effect of additional therapy with aliskiren on vascular parameters were documented. When analyses were restricted to patients with vascular remodeling, defined by median of WLR >  = 0.33 (n = 60), WLR was significantly reduced after 8 weeks by the treatment with aliskiren compared to placebo (-0.04 ± 0.07 versus 0.0 ± 0.007, p = 0.029). Consistently, after 8 weeks of on-top treatment with aliskiren there was an improvement of PP amplification compared to placebo (0.02 ± 0.07 versus -0.02 ± 0.09, p = 0.050), indicative of less stiff arteries. Conclusions: Thus, our data indicate that treatment with aliskiren, given on top of valsartan therapy, improves altered vascular remodeling in hypertensive patients.